PENDAMPINGAN PENGOLAHAN SAMPAH ANORGANIK MENJADI BARANG BERGUNA DI DESA JELANTIK - Almusyarofah, Syayidatina Fajriyah; Goro, Alfarizal; Syakila, Ahlul Royani; Zanjabil, L. M. Khadafi; Juang, Genta; Nova, Baiq Nazzura Desfi; Syalsabila, Lilla; Ramadhani, Sagita Nurul; Shufairo, Wiwik Ramdhaini; Sakinah, Riska (Jurnal Wicara, 2024)
Jelantik Village is a village in Jonggat Sub-district, Central Lombok Regency that has a waste problem. Until now, there has been no landfill in the village due to land constraints that are not yet available. As a result, a lot of garbage is dumped on the side of the road, especially at each bridge. This KKN program aims to do service in solving village problems together in the field of creative economy. KKN PMD University of Mataram Jelantik Village held a main work program in the form of processing and utilizing inorganic waste into goods that can be reused into ecobricks.